2020
DOI: 10.1021/acs.organomet.9b00851
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Active Glycol Nucleic Acid (GNA) Components: Synthesis and Properties of the Ferrocenyl-GNA Nucleoside, Phosphoramidite, and Semicanonical Dinucleoside Phosphate

Abstract: Ferrocenylated glycol nucleic acid (Fc-GNA) components are rarely studied in the field of xeno nucleic acid (XNA) chemistry. As an attempt to contribute to XNA chemistry, in the present article we report a seven-step synthesis of the first semicanonical dinucleoside containing the Fc-GNA nucleoside linked to the adenosine nucleoside with a phosphodiester bond. First, the nucleoside-bearing ethynylferrocenyl moiety in the C5 position of the uracil nucleobase was obtained. In the following steps, the nucleoside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Conjugation of the redox-active ferrocenyl entity with nucleic acids and their constituents has been proved as an effective approach for bioanalytical applications. [32,33,[50][51][52][53][54] The Fc-XNA oligonucleotides [38] as well as some Fc-GNA [43,44,46] and Fc-PNA [35,55] constituents have also been studied by electrochemistry. To achieve complete spectroscopic characterization with electrochemical data, the compounds (R,R)-1, (S,R)-1, and (R,R)-2 were subjected to cyclic voltammetry (CV).…”
Section: Electrochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Conjugation of the redox-active ferrocenyl entity with nucleic acids and their constituents has been proved as an effective approach for bioanalytical applications. [32,33,[50][51][52][53][54] The Fc-XNA oligonucleotides [38] as well as some Fc-GNA [43,44,46] and Fc-PNA [35,55] constituents have also been studied by electrochemistry. To achieve complete spectroscopic characterization with electrochemical data, the compounds (R,R)-1, (S,R)-1, and (R,R)-2 were subjected to cyclic voltammetry (CV).…”
Section: Electrochemistrymentioning
confidence: 99%
“…Approach I involves the substitution of glycol hydrogen atom in position 3' with either an Fc [44] or a pyrenyl [45] entity, while approach II is based on the introduction of an Fc moiety in position 5 of the base. [46] These approaches allowed us to obtain the redox-active Fc-XNA nucleosides B and D as well as luminescent derivative C. It is worth noting that nucleoside D proved its usefulness in the preparation of semicanonical dinucleoside phosphate E (Figure 1), [46] while pyrenyl nucleoside C was used for HeLa cell imaging with confocal microscopy. [45] Our expertise in Fc-GNA and bioorganometallic chemistry [47,48] enabled us to further explore the synthetic chemistry of Fc-GNA constituents and study their activity against cancer and noncancerous cells.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Kowalski and coworkers published the synthesis of a ferrocenyl-labeled analog of the nucleoside GNA-U (GNA-Fc U, 24, Chart 7) [55]. Cyclic voltammetry studies of a chimeric dinucleoside phosphate (GNA-Fc U)p(rA 2 ,3 -O,O-isopropylidene ) revealed the presence of a one-electron ferrocenyl-centered redox wave.…”
Section: Glycol and Butyl Nucleic Acids (Gna And Buna)mentioning
confidence: 99%
“…Therefore, we attempted to synthesize this new class of compounds as part of our research on the chemistry and biology of organometallic nucleic acid components. 49,50…”
Section: Introductionmentioning
confidence: 99%